2013
DOI: 10.1186/1476-072x-12-28
|View full text |Cite
|
Sign up to set email alerts
|

Mapping HIV clustering: a strategy for identifying populations at high risk of HIV infection in sub-Saharan Africa

Abstract: BackgroundThe geographical structure of an epidemic is ultimately a consequence of the drivers of the epidemic and the population susceptible to the infection. The ‘know your epidemic’ concept recognizes this geographical feature as a key element for identifying populations at higher risk of HIV infection where prevention interventions should be targeted. In an effort to clarify specific drivers of HIV transmission and identify priority populations for HIV prevention interventions, we conducted a comprehensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
88
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(97 citation statements)
references
References 24 publications
7
88
0
2
Order By: Relevance
“…We identified spatial clusters of high and low HCV prevalence, as well as spatial clusters of high and low PAT exposure, using a spatial scan statistical analysis, implemented in the SaTScan software . Scan statistics are one of the most widely used statistical methods for cluster detection in epidemiology . Briefly, scan statistical analysis uses circular windows of varying radii that span the study region to identify areas with exposure clustering.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified spatial clusters of high and low HCV prevalence, as well as spatial clusters of high and low PAT exposure, using a spatial scan statistical analysis, implemented in the SaTScan software . Scan statistics are one of the most widely used statistical methods for cluster detection in epidemiology . Briefly, scan statistical analysis uses circular windows of varying radii that span the study region to identify areas with exposure clustering.…”
Section: Methodsmentioning
confidence: 99%
“…19,20 Scan statistics are one of the most widely used statistical methods for cluster detection in epidemiology. 21,22 Briefly, scan statistical analysis uses circular windows of varying radii that span the study region to identify areas with exposure clustering. Since we aimed to identify localized clusters, a maximum circular window of 30 Km in radius was used for scanning clusters of HCV exposure and PAT exposure.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, there is growing evidence on the use of geographic clustering of HIV infections as a means to identify populations at higher risk of HIV infection, and subsequently targeting HIV prevention efforts on priority geographic areas to maximize the impact on the HIV epidemic [3]. In Nigeria, it is estimated that the key populations considered to be most at risk for HIV transmission, Female Sex Workers (FSWs), Injecting Drug Users, and Men who have sex with Men and their partners contribute as much as 40% of new HIV infections, despite representing only about 3.4% of the adult population.…”
Section: Introductionmentioning
confidence: 99%
“…As the innovation diffusion perspective would posit, widening access to HIV/AIDS services should lead to increased utilization of those services. Given the growing availability of spatial data and advances in spatial analysis techniques, as well as worldwide concern about the challenges posed by HIV/AIDS to public health, it is not surprising that GIS is increasingly adopted to support analysis of HIV-related outcomes (Kandwal et al, 2009; Cuadros et al, 2013). For example, Tanser et al (2000) found that geographic access is a vital determinant of HIV heterogeneity in rural South Africa.…”
Section: Introductionmentioning
confidence: 99%